DESAIN DISPLAY MERCHANDISE IDOL GROUP KOREA TWICE - Ahmad Nur Rizky Firmansyah; Ningroom Adiani (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2021)
The development of South Korean culture is currently very popular among teenagers, women or men. K-Pop Group Twice is one of the results of South Korean culture. Twice Group K-Pop fans also want to have idol-themed goods. Every collection owned by collectors is always exhibited or sold at local Twice Group K-Pop events. At the event, displays are used for promotional media for collection products to be sold. Based on this, facilities are needed to facilitate collectors in product promotion media in the form of booths or display collections of products that can be used during events. The research method used to find data, used a mix of qualitative and quantitative methods, namely observing in various places related to display design, and conducting interviews with several members of the k-pop idol group community and collectors. In analyzing the design analysis used, the order of analysis is as follows: needs analysis, space analysis, display analysis, ergonomics analysis, anthropometric analysis, arrangement analysis, placement analysis, shape analysis, color analysis, system analysis, material analysis, and finishing analysis. which is on the display design for the placement of the collector's merchandise collection. The results of the analysis show that the product has an elegant design concept and displays the shape of the characteristics that the k-pop idol Twice always brings. This display can make it easier for visitors when they want to find a collection of merchandise at events and the display can also be used at home as a placement for other collectors' collections.